HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR PENJASORKES SISWA SD NEGERI 006 SUNGAI SEGAJAH KECAMATAN KUBU - ', Al Amin; ', Ramadi; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the low penjasorkes learning outcomes result on students SDN 006 Segajah Sungai Kubu district. From some students found scores did not reach KKM. This problem is evident from observations of researchers during the learning and exams, it is suspected because of the nutritional status held by students. Therefore, the purpose of this study was to determine the corelation between nutrition status with the penjasorkes learning outcomes of students of SDN 006 Sungai Segajah. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is the nutrition status, while the dependent variable (Y) is the penjasorkes learning outcomes result. The research data was obtained from measurements of height and weight of students, and the value of MID Penjasorkes. The sample in this study were students siswa-siswi class V SDN 006 Sungai Segajah totaling 34 (purposive sampling). Based on the research results can be concluded as follows: From the results obtained the nutritional status of 34 students of SD Negeri 006 Sungai Segajah District of Kubu shows that the nutritional status of 14 people or 41% of students have a normal nutritional status in the category. Penjasorkes learning outcomes of 34 students of SD Negeri 006 Segajah Sungai Kubu district that 10 people or 29% showing in the category enough. From the results obtained nutritional status are significant corealtion with penjasorkes learning outcomes SDN 006 Segajah Sungai Kubu district students, characterized by the results obtained by the rhitung 0.54> ttabel 0,339.Keywords : Nutrition Status, Penjasorkes, Learning Outcomes